(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
By the interaction of the hydrochloric salts of 3-(4-hydroxy-2-methylquinol-3-yl)propionic acids chloranhydrides with o-aminophenole, o-phenylenediamine and o-mercaptoaniline the corresponding 2-[(4-hydroxy-2-methylquinol-3-yl)ethyl]-1,3-benzoxazoles, -benzimidazoles and -benzthiazoles were synthesized.